Solid waste recycling within higher education in developing countries: a case study of the University of Lagos - Mbama, Charles A.; Otegbulu, Austin; Beverland, Iain; Beattie, Tara K. (Journal of Material Cycles and Waste Management, 2023)
To create a truly circular economy requires a shift from the traditional view of waste disposal to one of resource management. This is particularly important in developing countries, where municipal waste generation is increasing, and efficient recovery of economic value from waste is rarely achieved. Conducted in the University of Lagos (UoL), Nigeria, this study investigated the efficiency of a recycling scheme with the goal of making recommendations to improve the process. UoL’s recycling policy centers around source segregation of waste into color-coded bins. Waste audit was carried out using the output method and interviews were conducted with staff from the waste management team to understand practices on campus. Substantial contamination of colored bins with non-target material was observed. Organics (30%), mixed plastics (28%) and paper (24%) were the most abundant materials, hence have the greatest potential for recovery, and income generation, if segregation rates could be improved. Despite its recycling policy and infrastructure, 99% of UoL waste was going to landfill. Poor policy implementation results in low recovery rates. Targeted waste reduction and increased material recovery would enhance efficiency. Improved awareness of recycling benefits, in addition to policy enforcement, could serve as tools to increase stakeholder participation in recycling.
Keywords: Municipal solid waste; Recycling; Waste characterization